PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH, PENERAPAN STANDAR AKUNTANSI PEMERINTAH DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH; SISTEM PENGENDALIAN INTERN PEMERINTAH SEBAGAI PEMEDIASI - Annie Mustika Putri; Kirmizi Kirmizi; Yesi Mutia Basri (Jurnal Ekonomi, 2016)
This research aims to test the influence of directly and indirectly the independentvariables of the application of the system financial accounting areas, application of government accounting standards, competencies of human resources, dependent variable quality of local government financial reports with variable mediation internal control system the government. The data used in this research is the primary data that comes from the dissemination of questionnaires to officials administering finance in a work unit (SKPD) area of the device in the city of Pekanbaru, Kampar and Rokan Hilir. The SEM analysis approach through partial least square (PLS). The results showed that implementation of the Government's accounting standards, and the competence of the human resources of the positive and significant effect, either directly or indirectly to the quality of the financial report of local government through the intervening variables, the system internal control of the Government. While the variable the application of the system financial accounting areas does not affect the of the financial reports of local government.